2012
DOI: 10.1002/art.34589
|View full text |Cite
|
Sign up to set email alerts
|

Circulating fibrocytes contribute to the pathogenesis of collagen antibody–induced arthritis

Abstract: Objective. Rheumatoid arthritis (RA) is a systemic autoimmune disease resulting in joint inflammation. Fibroblast-like synoviocytes in affected joints are responsible for pannus formation and cytokine/ chemokine production, resulting in leukocyte recruitment and bone/cartilage destruction. Previously, we identified a multipotent stem cell population of activated fibrocytes in the blood of patients with RA that may have a role in disease pathogenesis, perhaps as fibroblast-like synoviocyte precursors. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 53 publications
5
43
0
Order By: Relevance
“…4, Supplemental Digital Content 5, http://links.lww.com/ CCM/B688). Several studies also suggest a strong link between inflammation and fibrocyte differentiation (13,(29)(30)(31). Concordantly, we demonstrated that exposition of monocytes to corticosteroids in vivo or in vitro completely inhibited their (Fig.…”
Section: Blood Monocytes' Ability To Differentiate Into Fibrocytes Issupporting
confidence: 75%
“…4, Supplemental Digital Content 5, http://links.lww.com/ CCM/B688). Several studies also suggest a strong link between inflammation and fibrocyte differentiation (13,(29)(30)(31). Concordantly, we demonstrated that exposition of monocytes to corticosteroids in vivo or in vitro completely inhibited their (Fig.…”
Section: Blood Monocytes' Ability To Differentiate Into Fibrocytes Issupporting
confidence: 75%
“…Fibrocytes migrate to sites of tissue injury in response to chemokines [1, 6, 7] and regulate site-specific inflammation and fibrosis through antigen-specific T cell stimulation [8], cytokine production [9], extracellular matrix remodeling [10], and differentiation into other cell types such as adipocytes and myofibroblasts [11, 12]. Fibrocytes have been implicated in a myriad of inflammatory and fibrotic conditions in the lung [2, 3, 7, 13], liver [14], kidney [15], heart [16], vasculature [17, 18], joints [19], and skin [20, 21]. Accumulating evidence suggests that they also play an important role in the pathogenesis of Graves disease (GD) and Graves orbitopathy (GO).…”
Section: Introductionmentioning
confidence: 99%
“…Fibrocytes are bone marrow derived progenitor cells with the ability to differentiate down mesenchymal cell lineages [35]. They have been implicated in many pathologic processes of chronic inflammation and fibrosis, including arthritis, chronic kidney disease, scleroderma, asthma, and idiopathic pulmonary fibrosis [3, 4, 68]. They originate in bone marrow, mobilize into the circulation in response to inflammatory chemokines, and home to sites of inflammation.…”
Section: Introductionmentioning
confidence: 99%